Pengaruh Pelatihan kerja dan Kompensasi Terhadap Kepuasan Kerja Serta Dampaknya Terhadap Prestasi Kerja Karyawan Koperasi Serba Usaha Kuta Mimba Di Kuta-Badung - Giritama, I Putu Candra; Suana, I Wayan (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
The purpose of this research is to know how much influence the compensation and job training to job satisfaction and great influence of job training, compensation and job satisfaction of the employee Cooperative achievements All-round Effort Mimba Kuta. This research was conducted in a cooperative Effort All-round Mimba Kuta by using all employees as respondents. The number of respondents in this study of 75 people. The technique used is the analysis of path analysis (path analysis) considering the research aims to find the great influence of endogenous variables exogenous to the between variables. The research found that job training and compensation effect significantly to job satisfaction of employees. job training, compensation and job satisfaction influence positively and significantly to the achievements of the work of employees . Keywords : job training, compensation, job satisfaction and work performance
Keywords: job training, compensation, job satisfaction and work performance